Aiding risk information learning through simulated experience (ARISE): Using simulated outcomes to improve understanding of conditional probabilities in prenatal Down syndrome screening. Issue 10 (October 2017) - Wegier, Pete; Shaffer, Victoria A.
Highlights: Simulated experience improves understanding of the PPV of diagnostic screening tests. Simulated experience decreases interest in undergoing Down syndrome screening. Concern over a positive test result declined when learning via simulated experience. Abstract: Objective: To determine whether the use of visually-presented simulated experiences to communicate statistical information can improve an individual's understanding of conditional probabilities—specifically the positive predictive value (PPV) of prenatal screening tests for Down syndrome. Methods: In Experiment 1 ( N  = 64) and Experiment 2 ( N  = 180) participants were asked to estimate the PPV of a prenatal screening test for Down syndrome based on either (1) explicit statistics regarding the prevalence of Down syndrome and the sensitivity and specificity of a prenatal screening test for Down syndrome, or (2) experiencing up to 5000 simulated test results over a short time. Results: Participants' estimates of the PPV were more accurate when they had learned via simulated experiences (79% accuracy) compared with estimates based on explicitly described statistics (14%). Participants in the simulated experience condition also reported decreased interest in screening and decreased concern with a positive test result. Conclusion: A visual paradigm presenting simulated experiences improves PPV estimates, compared to estimates derived from explicitly provided statistics, while also shifting attitudes away from screening. Practice implications: The use of simulated experiences may prove to be simple but powerful tool to communicate complex statistical information to patients in medical decision making situations.